Willingness to Communicate and English Speaking Performance: A Phenomenological Study of Tadulako University EFL Students - Reza, Mutia; Hastini, Hastini; Sadilia, Sukmawati; Marhum, Mochtar (Journal of English Language and Education, 2025)
Willingness to communicate (WTC) has emerged as a critical psychological construct mediating between linguistic competence and actual language use, yet its influence on speaking performance remains underexplored in Indonesian EFL contexts through learners' lived experiences. This qualitative study employs Interpretative Phenomenological Analysis (IPA) to investigate how English Education students at Universitas Tadulako experience and interpret the ways WTC shapes their English-speaking performance. Three undergraduate students (semesters 3-5) participated in in-depth semi-structured interviews, with findings triangulated through a lecturer interview. Systematic IPA analysis revealed four superordinate themes: (1) WTC as Dynamic Social-Cognitive State, fluctuating with context rather than functioning as a stable trait; (2) The Fluency-Accuracy Paradox, whereby students universally prioritize comprehensibility over grammatical correctness as a strategic coping mechanism; (3) Fear as Cultural-Pedagogical Construct, wherein judgment anxiety rooted in Indonesian educational culture inhibits WTC despite supportive teaching; and (4) The Preparation Imperative, in which advance notice and cognitive readiness universally facilitate WTC while spontaneous demands trigger defensiveness. Findings demonstrate that WTC operates as a multi-dimensional construct shaped by individual motivation, social ecology, cultural context, and pedagogical environment. Practical implications include creating psychologically safe environments, validating fluency-first strategies, and scaffolding spontaneity through preparation.